ANALISIS KINERJA RUKUN TETANGGA (RT) DIKELURAHAN JAYAMUKTI KOTA DUMAI - Isnaini, Isnaini (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
: Jaya Mukti is one of the sub-districts in Dumai Timur District East Dumai Urban Village Jaya Mukti is one of urban villages located in the middle of Dumai City with the highest population density among urban villages in Dumai City. To realize JayaMukti Village Mission, Kelurahan is assisted by the performance of the existing Chairman of the RT, and coincides with the respective term of each Chairman of the RT ended in March 2017 then the researcher made a research on how the Head of RT in JayaMukti Kota Dumai by Payaman J. Simanjuntak "(2005: 1) Is a level of achievement of the results of the implementation of certain tasks. "And Prawirosentono in Sinambela (2012: 5) performance is the work that can be achieved by a person or group of people within an organization, in accordance with the authority and responsibility of each, See that the outcomes of the results or the implementation of the task of Chairman of the RT has not been optimal. Research was chosen purposively in JayaMukti Subdistrict, Kecamtan Dumai Timur Kota Dumai with qualitative approach and data collection technique by interview, observation and documentation. Respondents only 16 Head of RT from 23 RT , Key Informant is Lurah Jayamukti.serta Kasi Pemerintahannya.hasil Research is Performance Chairman of RT in Kelurahan JayaMukti from Administration Reporting that maximal routine only reaches 50%, Increase participation of citizen or citizen in Village JayaMukti average 72,50% for , Community empowerment or average citizen of 26.56% and Maintenance of Public Security and Order of the Community Average of 43.75%. To improve the performance of Ketau RT in addition to increasing the capacity of the RT Chairman himself and realizing that the position of Chairman of the RT is a Social , So the consciousness of the consequences, while the community must be educated about the social function as Chairman of the RT while from the Village can make a kind of integrity fact that must be signed by the Head of RT in Kelurahan so there are things that need to be accounted for according to the fact of integrity.